Distribution of iron and zinc in plant and grain of different rice genotypes grown under aerobic and wetland conditions - Saenchai C. (2017)
© 2016 Elsevier Ltd This paper examined the distribution of Fe and Zn in the plant and seed of different rice genotypes in different growing conditions. The Fe and Zn concentrations were determined in different plant tissues during the growth stages of 3 genotypes with high Fe and Zn check genotypes, and in different grain tissues of 15 genotypes grown in aerobic and wetland conditions. Iron and Zn were distributed differently in tissues of the rice plant, with the harvest index (panicle nutrient content as the % of the total above ground nutrients) at 3–4% for Fe and 54–74% for Zn. The concentrations of both Fe and Zn of the endosperm increased with the increasing proportion of the grain nutrient content allocated to the endosperm, but declined when the allocation to the bran fraction increased. The Fe concentrations of the de-husked caryopsis of rice grown in the aerobic soil and the Fe concentration of the de-husked caryopsis of rice grown in the wetland soil were closely related, but not in the endosperm Fe, while the grain Zn concentrations in the aerobic soil were found to correlate with the Zn concentrations in the wetland soil for both the de-husked caryopsis and the endosperm.